Urban Mobility and Polluting Emissions: Impacts on Public Welfare - Fistola, Romano; Gallo, Mariano; La Rocca, Rosa Anna (TeMA - Journal of Land Use, Mobility and Environment, 2009)
This article introduces the problem of assessing urban effects of air pollution produced by road traffic and it is oriented to individualize the "critical" areas where it is necessary to intervene in order to optimize the security levels for public wellbeing. The research is targeted to assess the effects of pollutant emissions, particularly of PM10, on human health by testing methodology at three different territorial levels (regional, provincial, municipal). In this article we refer particularly to the city of Benevento and we propose to point out a methodology for identifying critical infrastructure where it is necessary to restrict vehicular traffic. The target of this study is the identification of urban ambit characterized by high levels of risk to public health arising from the mobility vehicle. Prerequisite is the consideration that the effects of pollutants are linked with urban morphology in particular the physical structure of the road network. In other word, within the city it is possible to identify "critical channels" where safety levels for human health are strongly compromise by their physical structure. The test has been referred to Benevento by using GIS to identify urban areas where high levels of risk due to pollutant emission concentrate. Gis has been projected to allow both the identification of “maximum risk areas” and the "critical channel" within the city.